Bridging Generational Gaps in Teachers’ Digital Literacy: A Systematic Review on Educational Leadership and Performance - Dedy Achmad Kurniady; Aan Komariah; Zaini Hafidh; Liris Raspatiningrum; Anisa Isti Yuslimah; Sururi Sururi; Novebri Novebri; Riyaldi Dithia Permana (Universitas Negeri Padang, 2026)
The rapid digital transformation in education has exposed a clear generational gap among teachers in mastering digital literacy. Younger teachers tend to navigate technology with greater ease, while senior teachers often encounter barriers that affect their confidence and classroom performance. This study aims to explore how educational leadership can help bridge this generational divide and enhance teachers’ digital competence. Adopting a systematic literature review guided by the PRISMA framework, the analysis covered studies published between 2020 and 2025 from major databases, including Scopus, Web of Science, and ERIC. The findings show that leadership practices emphasizing empathy, collaboration, and continuous learning are most effective in reducing generational gaps and fostering inclusive digital competence. However, existing frameworks rarely integrate generational diversity, leadership behavior, and performance management within one conceptual model. This study introduces the concept of Adaptive Intergenerational Leadership (AIL), a synthesis that combines transformational and adaptive leadership principles to foster bidirectional learning between digital native and digital immigrant teachers. The results contribute to educational leadership theory and offer practical implications for developing inclusive, innovative, and human centered school ecosystems in the digital era.